Evaluating new species for aquaculture: A genomic dissection of growth in the New Zealand silver trevally (Pseudocaranx georgianus) - Noemie Valenza-Troubat; Elena Hilario; Sara Montanari; Peter Morrison-Whittle; David Ashton; Peter Ritchie; Maren Wellenreuther (John Wiley & Sons Ltd., 2025)
Aquaculture is the fastest-growing food production sector worldwide, yet industry has been slow to implement genomic techniques as routine tools. Applying genomics to new breeding programmes can provide important information about pedigree structure and genetic diversity; key parameters for a successful long-term breeding programme. It can also provide insights on potential gains for commercially important, yet complex, quantitative traits such as growth rate. Here we investigated a population of 1100 captive-bred F1 silver trevally (Pseudocaranx georgianus), a promising new species for New Zealand aquaculture. We used whole-genome information, coupled with image-based phenotypic data collected over two years, to build the pedigree of the population, assess its genetic diversity, describe growth patterns of ten growth traits and estimate their genetic parameters. Successful parentage assignment of 664 F1 individuals showed that the pedigree consisted of a complex mixture of full-and half-sib individuals, with skewed reproductive success among parents, especially in females. Growth patterns showed seasonal fluctuations (average increase across all traits of 27.3% in summer and only 7% in winter) and strong inter-family differences. Heritability values for growth traits ranged from 0.27 to 0.76. Genetic and phenotypic correlations between traits were high and positive, ranging from 0.57 to 0.94 and 0.50 to 1.00 respectively. The implications of these findings are threefold: first, the best on-growing conditions are in warmer months, where highest growth peaks can be achieved; second, size-and family-based selection can be used as early selection criterion if pedigree structure and inbreeding risks are closely monitored; third, selection for body length results in concomitant increases in height and weight, traits of paramount importance for aquaculture. It is concluded that there is substantial potential for genetic improvement of economically important traits, suggesting that silver trevally is a promising species for selective breeding for enhanced growth.